The fabrication, characterization, and application of chitosan–NaOH modified casein nanoparticles and their stabilized long-term stable high internal phase Pickering emulsions. Issue 3 (20th January 2022) - Liu, Jingbo; Guo, Jian; Zhang, Hui; Liao, Yinan; Liu, Shuaiyan; Cheng, Dahao; Zhang, Ting; Xiao, Hang; Du, Zhiyang
Abstract : Schematic illustration of the chitosan–NaOH modified casein nanoparticles under different pH values and the applications of their stabilized long-term stable high internal phase Pickering emulsions. Abstract : The demand for facile delivery systems from natural biopolymers with long-term storage stability to deliver liposoluble nutraceuticals such as β-carotene (BC) is increasing. In this work, a facile and reliable emulsifier of chitosan (CS)–NaOH-modified casein (CA) nanoparticles (NPs) was fabricated for the stabilization of high internal phase Pickering emulsions (HIPPEs) with versatile stability. Dynamic light scattering, TEM, FTIR, and interface tension results indicated that CS–CA NPs exhibited nanoscale (109–373 nm), positive charge (22–38 mV), pH-response, spherical in shape, assembled spontaneously by non-covalent interactions, and high surface activity. Optical microscopy, confocal laser scanning microscopy (CLSM), and rheometer results demonstrated that HIPPEs were emulsified by a dense and compact 3D network between the continuous phase and the interfacial region. Hence, the CS–CA NP-stabilized HIPPEs showed long-term storage stability (over 18 months at ambient temperature) and thermostabilization (1 month at 80 °C). The robust and compact CS–CA NPs dramatically declined the contents of primary and secondary oxidation production in HIPPEs than that by corn oil. Moreover, CS–CA NPs stabilized HIPPEs appreciably enhanced the bioaccessibility (2.56 times) and chemical stability (thermal, UV-light, and storage) of BC. This research evidenced that CS–protein or polysaccharide–CA-based systems could be an encouraging formulation to commercially construct tunable HIPPEs with adorable stability for liposoluble nutraceuticals with enhanced attributes.